2015
DOI: 10.1187/cbe.14-12-0221
|View full text |Cite
|
Sign up to set email alerts
|

Online Resources for Understanding Outbreaks 
and Infectious Diseases

Abstract: Disease outbreaks can be a powerful topic for teaching about science and health. This Feature reviews resources for bringing up up-to to-date information on this hot topic into the classroom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…EID thus falls under two major categories—newly emerging and reemerging infectious diseases. Newly emerging infections refer to diseases that have been discovered in the human host or a population for the first time; reemerging infectious diseases can be defined as infectious diseases that reappear, usually in more pathogenic form and in rapidly increasing incidence or new geographic locations after apparent control or eradication [ 6 , 7 ]. Emerging infections (EIs) have featured prominently in the course of human history; they have caused inestimable harm to humanity [ 16 ].…”
Section: Emerging Infectious Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…EID thus falls under two major categories—newly emerging and reemerging infectious diseases. Newly emerging infections refer to diseases that have been discovered in the human host or a population for the first time; reemerging infectious diseases can be defined as infectious diseases that reappear, usually in more pathogenic form and in rapidly increasing incidence or new geographic locations after apparent control or eradication [ 6 , 7 ]. Emerging infections (EIs) have featured prominently in the course of human history; they have caused inestimable harm to humanity [ 16 ].…”
Section: Emerging Infectious Diseasesmentioning
confidence: 99%
“…Infectious diseases arise upon contact with an infectious agent. Five major infectious agents have been recognized, namely, bacteria, viruses, fungi, protozoa, and helminths [ 7 , 51 ]. Various factors can be identified that create opportunities for infectious agents to invade human hosts.…”
Section: Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, virtual exercises and complex computer simulations which incorporate network models have been used as teaching tools ( Huang et al, 2010 , Neulight et al, 2007 , Hsieh et al, 2006 ). Furthermore, there are now numerous interactive online teaching resources that allow the user to ‘solve’ outbreaks by playing the epidemiologist ( Barber and Stark, 2015 , CDC, 2017b , Center for Technology in Teaching and Learning, Rice University, 2017 ). The University of Cambridge provides a selection of online games where the aim of the game is to infect as many people as possible using the characteristics of a specific infectious disease such as influenza ( Cambridge Infectious Diseases, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous resources and simulations are available highlighting infectious diseases and vaccination ( 1 3 ). The spread of infectious diseases is often simulated using the pH indicator phenolphthalein to trace a basic solution as the infectious agent ( http://www.pbs.org/newshour/extra/app/uploads/2014/09/1_Epidemics-NGC.pdf ).…”
Section: Introductionmentioning
confidence: 99%